Abbasi Devletinde hanedan krizi ve ilk iç savaş (H.175-198/M.791-813) - Dalkılıç, Mehmet (İlahiyat Yayınları, 2015)
[No Abstract Avilable]
1.bs.
Keywords: Tarih; Tarih; Ortadoğu; 640-1000; Abbasi Devleti